Critical Effect of Oxygen Concentration and Acidity on the Efficiency of Photodegradation of Levofloxacin with Solar UVB Light; Cytotoxicity on Mammalian Cells of the Photoproducts and Its Activity on Pathogenic Bacteria - Biondi, Macarena Agostina (2025)
Levofloxacin is an antibiotic classified as an emerging contaminant. Its presence in aquatic environments represents potential risks to ecosystems and human health, making its removal during wastewater treatment of relevant importance. Here, we present a comprehensive kinetic analysis of levofloxacin photodegradation under UVB solar irradiation, with emphasis on the influence of pH and dissolved oxygen, two conditions that can vary widely in wastewater and impact treatment efficiency. We also investigated the formation and role of reactive oxygen species in the degradation mechanism, as well as the cytotoxicity and antibacterial activity of photoproducts. Our findings reveal that the efficiency of levofloxacin photodegradation is highly dependent on environmental conditions; it requires neutral or slightly alkaline pH and a high concentration of dissolved oxygen, a situation not always observed in contaminated waters. Several reactive oxygen species are generated, with singlet oxygen being the most reactive with the antibiotic. We report for the first time the singlet oxygen quantum yield from levofloxacin. Bioassays demonstrated that photoproducts neither exhibit antibacterial activity nor induce significant cytotoxicity. Our study suggests that UVB treatment of contaminated effluent containing levofloxacin could be an effective and environmentally safe strategy for the antibiotic degradation under certain conditions of pH and dissolved oxygen.